TLR-4 Inhibition Attenuates Inflammation, Thrombosis, and Stenosis in Arteriovenous Fistula in Yucatan Miniswine - Rai, Vikrant; Radwan, Mohamed M; Nooti, Sunil; Thankam, Finosh G; Singh, Harbinder; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2022)
Arteriovenous fistula (AVF) is the preferred vascular access in hemodialysis patients; however, it is afflicted with a high failure rate. Chronic inflammation, excessive neointimal hyperplasia (NIH), vessel stenosis, early thrombosis, and failure of outward remodeling are the major causes of AVF maturation failure. Inflammatory mediator tolllike receptor (TLR)-4 plays a critical role in NIH, arterial thrombosis, and stenosis. We investigated the effect of TLR-4 inhibition on early thrombosis. Yucatan miniswine were used to create AVF involving femoral artery and femoral vein and treated with TLR-4 inhibitor TAK-242 with ethanol as the vehicle. The vessels were assessed after 12 weeks using histomorphometry, immunostaining, ultrasound, angiography, and optical coherence tomography. Inhibition of TLR-4 attenuated inflammation and early thrombosis in 50% of animals, and blood flow was present through AVF in 25% of animals. Thus, targeting TLR-4 to attenuate inflammation and early thrombosis might be a therapeutic approach to keep AVF patent and maintain blood flow through the outflow vein.